Absolution - McDermott, Alice (Farrar, Straus and Giroux, 2023)
In Saigon in 1963, two young American wives form a wary alliance. Tricia is a starry-eyed newlywed, married to a rising oil engineer "on loan" to US Navy Intelligence. Charlene is a practiced corporate spouse and mother of three, a talented hostess and determined altruist, on a mission to relieve the "wretchedness" she sees all around her. When Tricia miscarries, Charlene sweeps her into a cabal of well-dressed do-gooder American wives. Armed with baskets filled with candy and toys, they descend on hospitals, orphanages, and a leper colony on the coast, determined to relieve suffering, no matter the cost. Sixty years later, Charlene's daughter reaches out to Tricia, now widowed and living in Washington. As the two relive their shared experience in Saigon, they are forced to come to terms with the ways their own lives have been shaped and stunted by Charlene's pursuit of "inconsequential good."